Distribución espacial de la comunidad de aves en la Microcuenca MISHQUIYAQUILLO ACM Almendra, San Martín - Altamirano Guerrero, José Oriel (2010)
The present thesis, “Space Distribution of the Community of Birds in the Micro- hollow Mishquiyaquillo ACM Almond, San Martin”, this oriented to contribute with information on the identification of the community of birds and its space distribution in the Mishquiyaquillo micro-hollow. The identification of the community of birds, settled down at random with count points (30 points), for which I am already used established footpaths that cross by representative zones of the area in study. It was decided on this method due to the sizes of the registered areas and for being these easily visible. For the observation and identification of the birds it was used binoculars (8 xs 42) and guides of field (Thomas S. Schulenberg, 2007 and Clements & Shany, 2001), having one distance average of observation of 50 M.s the round one, by a period of time by each point of 10 minutes. In each count they were registered: species, number of individuals and frequented vegetal formation. The samplings were carried out between June of the 2008 and January of the 2009 with 5 days of sampling per month, sampling themselves 6 points per day. This work of field complement with a characterization of vegetation in each sampling point to determine the characteristics of the type of vegetation used by the species. For the analysis of distribution of the community of birds within the Mishquiyaquillo micro-hollow it was realised through the obtained data in the field of the Elements of Occurrence of the species of birds, also the intrinsic take into account the availability of resources and factors (behavior, competition) and extrinsic (environmental heterogeneity, allelopathy, depredation, etc.) that determine the location of each individual in the space; the vegetal types of formation and the altitudinales ranks. With the data available I determine the type of distribution for each species. In addition use became of the programs like: The ArcGis 9,3 and extracted satelite images of Google Earth, for the accomplishment of respective maps indicating the location of the species within the area. In order to work and to model the ranks of the species it was decided to divide the micro-hollow in loss, average and high taking like criterion the differences from altitude (low 900-1200, average 1200-1500 and high one of 1500-1620), the combination of the same (low and average 900-1500, average and high 1200 to 1600) and all the space of the micro-hollow (low, average and high 900- 1620); determining the number of species distributed in each vegetal formation in the different altitudinales ranks. The collected data were 332 species of birds pertaining to 15 you order, 42 families with 229 sorts, distributed in five formation vegetal different (Taken part Primary Forest, secondary Forest, Slope Forest, Cleared Plantations of Coffee and Areas). Of which 4 species are endemic for Peru, 17 migratory species, 15 species of restricted habitat, 67 species were outside their established rank and according to his categorisation one it is in danger, 4 species are vulnerable and 5 species are threatened. Being 319 species that present/display crowded together distribution and 13 with distribution at random. Also one was according to the altitudinales ranks and to the types of vegetal formation 204 species in Primary Forest, 183 species in Secondary Forest, 52 species in Slope Forest, 130 species in Plantations of Coffee and 36 species in Cleared Areas. This result is complemented with a proposal of plan of handling where the conservation concerning species, of habitat and genetic flow is prioritized, with its respective strategic targets that to fulfill